Theoretical and methodological approaches to the study of bases of formation of social activity of youth - E. V. Domashova; E. V. Blagovskaya; T. A. Gonohova (Вестник университета)
The article reveals the concepts of activity, youth, social activity. The paper notes great attention to young people, especially to the problems of young people, because youth is the most active age group, that can realize itself in all spheres of life: cultural, social, political etc. The authors notice that young people, more than other socio-demographic groups, are focused on raising their social status and on mastering new social roles. The article analyses theoretical approaches to the study of the foundations of the formation of social activity of young people: philosophical, pedagogical, psychological, and sociological. In addition, the paper notes availability of a huge number of author’s interpretations of the definition of «social activity». A common feature of the authors’ study of the phenomenon of activity is the presence of a purposeful, conscious, motivated impact of the personality on society. In addition, social activity is an integral part of the motivational structure of the individual. Based on the author’s interpretations of various scientists, the paper emphasizes the General characteristic of the definition of «social activity» – the presence of quantitative and qualitative characteristics of an individual’s social interaction with the surrounding world.